Pentecostal Reinventions of the Passover: Contextual Reflections on the End of Year Night Worship Festivals in Uganda - Alexander Paul Isiko; Enock Kisekka (Journal for the Study of Religion)
Pentecostal scholarship in and about Africa is a vibrant arena in world Christianity, with an upswing in the proliferation of scholarly works on Pentecostal Churches and its centrality in the political and social fabric of African societies. Pentecostalism has been hailed for revival of Christian conservatism in Sub-Saharan Africa, predominated by the nominal Roman Catholics and Protestant Christianity. While some authors have studied African Pentecostalism with prejudgments based on other Christian traditions, some have hailed the theological innovations in healing and evangelism. The study of the Pentecostal end of year worship festivals unravels one of the innovations that justifies the uniqueness of African Pentecostalism, promulgating theologies and traditions on the one hand, and reinventing Judeo-Christian practices in African perspectives, which in a sense give African Pentecostal Churches a claim to divine originality, on the other. In another way, theologies, traditions, and practices emerging from the observance of the annual Pentecostal worship festivals place African Pentecostal Churches among the towering African Christian traditions, which then borrow rather than debunk such Pentecostal theological innovations. This article therefore discusses the Pentecostal Church reinvention of the ancient Jewish Passover festival to mirror the lives of African Christians in contemporary contexts. The ‘contextual theology’ analysis is employed to reflect on both the Jewish Passover and annual Pentecostal worship festivals, with a view of establishing how Passover (non-)parallels and reinventions have produced African Pentecostal theologies, traditions, and practices defining the uniqueness of African Pentecostalism.